The Role of Withdrawal, Reward, and Leadership in Employee Engagement - Basneldi, Basneldi; Pasaribu, Rodeyar; Arini, Dewi Ulfa; Kamsariaty, Kamsariaty; Januarianto, Tri (Dinasti Publisher, 2025)
To find out the influence of withdrawal behavior, intrinsic rewards and transformational leadership style on employee engagement at the DKI Jakarta Provincial Regional Civil Service Agency. Using Structural Equation Modeling (SEM) Analysis to find out if there are a series of relationships affecting withdrawal behaviour, intrinsic rewards, transformational leadership and employee engagement or vice versa. The analysis tool used in this study is a linear regression analysis tool using a quantitative method using Structural Equation Modelling with the help of Lisrel 8.8 software. The compatibility test in this study was carried out on the coefficients of structural equations by specifying a certain level of significance. If the significance level is 0.05, then the t-value of the structural equation should ? 1.96. Thus, the research hypothesis is accepted if the absolute value of t (t-value) > 1.96, and the coefficient of the value of t (either positive or negative) according to the existing research hypothesis. The results of this study on the three hypotheses are all accepted. The results of this study are limited to the variables used. For the research object and the variables used in this study.